URGENSI SUPERVISI PENDIDIKAN DALAM PERSPEKTIF AL-QURAN SURAH ALI-IMRAN 110 & AL-BAQARAH 143 - Prasetyo, Dani; Patimah, Siti; Warisno, A.; Arafah, A. Latief Arung (FIKRAH, 2025)
Education in the digital era faces very tough challenges, both from character formation to the independence of a student which is still not visible. This research aims to identify educational supervision as an important aspect in achieving the goals of Islamic education. The Qur'an emphasizes the importance of supervision in forming character, improving the quality of education, and preventing mistakes. Therefore, the implementation of educational supervision that is effective and in accordance with the values of the Qur'an needs to be carried out to achieve this goal. The research results show the importance of (1) Periodic Supervision: Carrying out regular supervision to monitor the educational process. (2) Evaluation and Feedback: Provide constructive evaluation and feedback to improve the quality of education. Guidance and Counselling: Providing guidance and counseling to help students overcome difficulties. (3) Collaboration with Parents: Collaborating with parents to ensure harmony between education at school and at home.